VD_FINDINFO Décision / 2012 / 745 vom 6. Juli 2012 - VD Tribunal cantonal (2012)
FRAIS D'EXPERTISE, PLAIGNANT, ADMINISTRATION DES PREUVES, D'OFFICE | 139 CPP (CH), 184 al. 7 CPP (CH), 393 al. 1 let. a CPP (CH)